2019
DOI: 10.1021/acsami.9b06691
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot and One-Step Fabrication of Salt-Responsive Bilayer Hydrogels with 2D and 3D Shape Transformations

Abstract: Bilayer hydrogels are one of the most promising materials for use as soft actuators, artificial muscles, and soft robotic elements. Therefore, the development of new and simple methods for the fabrication of such hydrogels is of particular importance for both academic research and industrial applications. Herein, a facile, one-pot, and one-step methodology was used to prepare bilayer hydrogels. Specifically, several common monomers, including N-isopropyl acrylamide, acrylamide, and N-(2-hydroxyethyl)acrylamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Acrylamide (AAm, 99.0%) and N,N′-Methylenebisacrylamide (MBAA, 97%) were purchased from Aladdin reagent Inc. (Shanghai), The detailed synthesis route of dimethyl-(4-vinylphenyl) ammonium propane sulfonate (SVBA) can be found in our previous report ( He et al, 2019 ; Yuan H et al, 2021 ). In this experiment, all purified water was obtained from a Millipore system with an electronic conductance of 18.2 MΩ cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acrylamide (AAm, 99.0%) and N,N′-Methylenebisacrylamide (MBAA, 97%) were purchased from Aladdin reagent Inc. (Shanghai), The detailed synthesis route of dimethyl-(4-vinylphenyl) ammonium propane sulfonate (SVBA) can be found in our previous report ( He et al, 2019 ; Yuan H et al, 2021 ). In this experiment, all purified water was obtained from a Millipore system with an electronic conductance of 18.2 MΩ cm.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we ingeniously introduce a new structural salt-responsive zwitterion poly[3-(dimethyl(4-vinylbenzyl) ammonium) propyl sulfonate] (SVBA) into the polyAAm network to extend the practical candidates for the field of wound healing. The nature of polySVBA chains previously already presented unique salt-responsive properties and was applied to bacterial release ( Zhang et al, 2018 ; Wu et al, 2019 ), selective oil/water separation ( Wang et al, 2020 ), and thermal-induced soft actuators ( He et al, 2019 ), etc. Interestingly, rigid aromatic backbone and sequential ionic interactions synergistically promote surface bonding, potential conductivity, matrix stretchability, and self-healing properties.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the gradient compositional distribution of this asymmetric film is not determined by the different polymerization rate of monomers. [18,19] In order to go deeply into why bidirectional vapor-responsive with the opposite bending reaction can be achieved by the same method, we carefully reviewed all the factors that may influence the fabrication of film. It turned out that besides the P x B y formulations, the processing method of substrate, such as the employment of the untreated PP petri dishes or the one cleaned with lye, and even soaking time in the lye, could have a significant effect on the synthesizing of the asymmetric films.…”
Section: Uncontrollable Bidirectional Bending Vapor-responsive Filmmentioning
confidence: 99%
“…However, a porous asymmetric film generally has a weak mechanical strength. [ 20 ] Therefore, how to achieve a film with the well‐balanced mechanical strength and stimulus–response speed is essentially important for the design of smart stimuli‐responsive materials. Nature is the greatest teacher and we learned from it that two apparently contradictory elements can still be coordinated and unified.…”
Section: Introductionmentioning
confidence: 99%
“…Prepared bilayer hydrogels realized bidirectional bending properties under the stimulation of the salt solution. [14] Gao and co-workers developed a kind of bilayer thermoresponsive hydrogel actuators with curling/uncurling deformation property on the base of two-step molding in situ polymerization, which achieved snap-buckling motivated jumping under the stimulation of temperature. [15] Molding method owned the advantages of high polymerization efficiency, which prepared the hydrogel actuators with high mechanical strength successfully.…”
Section: Introductionmentioning
confidence: 99%